Living Dyslexia in the Foreign Language - Leite, Sónia Ruão (Advances in Social Sciences Research Journal, 2020)
English is an integral part of the curriculum of the Primary School, so we need to take a closer look at people struggling with problems in their mother tongue: the dyslexics. It is known that dyslexia is one of the factors associated with dropping out of school, depending the fluent reading on a series of cognitive factors that have to organize and work together to achieve their mastery. Any deficits that may arise at the level of these competencies will jeopardize the academic, personal and professional success of the dyslexic. We intended took a look at the errors made by these students in both languages and with the analysis of the results, which showed that they make the same errors in both languages, we intend to create pedagogical tools that allow these students to overcome the difficulties arising from their problems in English as a foreign language. This project has potential to contribute to one of the greatest current educational challenges, the re-education of the dyslexia in the foreign language through early intervention and phonological awareness training.